Implementasi Metode COPRAS Dengan Pembobotan ROC Dalam Menentukan Food Delivery Application Terbaik - Sihombing, Daniel Oktodeli; Yutika, Fitri; Cahyadi, Alex (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The food delivery application is a digital platform that allows users to order food from restaurants or other food vendors through smartphones or computers. Good service quality in the Food Delivery Application (FDA) has a positive and significant impact on customer loyalty to online food delivery services. Complex Proportional Assessment (COPRAS) is a multi-criteria decision-making method that has been extensively researched and applied in various fields. Weighting using the ROC method has proven to be highly effective in various research contexts. Data from 125 respondents used in this study were calculated using the COPRAS method and ROC weighting to generate rankings for each FDA. Service quality, promotions, features, costs, and UI/UX are criteria used in this calculation. The results of the calculation using the COPRAS method and ROC weighting show a slight difference, where alternative A1, GoFood, ranks first with a value of 0.55585381, followed by alternative A3, ShopeeFood, in second place with a value of 0.55584456, and alternative A2, GrabFood, in third place with a value of 0.55449330. Thus, the best FDA resulting from the calculation using the COPRAS method and ROC weighting is GoFood.